2007
DOI: 10.1176/ajp.2007.164.6.936
|View full text |Cite
|
Sign up to set email alerts
|

Therapist Affect Focus and Patient Outcomes in Psychodynamic Psychotherapy: A Meta-Analysis

Abstract: These data indicate that therapist facilitation of patient affective experience/expression is associated with patient improvement over the course of psychodynamic psychotherapy. Although the size of this relationship was not significantly related to methodological quality, results suggest the importance of close supervision of actual techniques through the use of audio- or videotapes. Additionally, results highlight the importance of defining outcome in a multidimensional way to properly assess theoretically r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
116
0
7

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(137 citation statements)
references
References 37 publications
(36 reference statements)
14
116
0
7
Order By: Relevance
“…Neurosciences significantly highlighted how relational our mind is [150] and that human beings are wired to be social [151]. Initial findings showed that shared emotions can synchronize brain activity [152]: from a meta-analytic studies of dynamic psychotherapies we now know that they are effective in several mental disorders [153] and that the more they consider affective and emotional aspects the more effective they are [154]. …”
Section: Discussionmentioning
confidence: 99%
“…Neurosciences significantly highlighted how relational our mind is [150] and that human beings are wired to be social [151]. Initial findings showed that shared emotions can synchronize brain activity [152]: from a meta-analytic studies of dynamic psychotherapies we now know that they are effective in several mental disorders [153] and that the more they consider affective and emotional aspects the more effective they are [154]. …”
Section: Discussionmentioning
confidence: 99%
“…In‐session emotional arousal and processing may be a key mechanism of change across therapy models and disorders (Greenberg & Pascual‐leone, ; Solbakken, Hansen, & Monsen, ; Whelton, ). For example, a number of process‐outcome studies have indicated that the degree of in‐session emotional activation is related to outcome in psychodynamic therapies (e.g., Diener, Hilsenroth, & Weinberger, ; Fisher, Atzil‐slonim, Bar‐Kalifa, Rafaeli, & Peri, ; Town, Lomax, Abbass, & Hardy, ; Town, Salvadori, Falkenstrom, Bradley, & Hardy, in press), as well as in emotion‐focused therapy (Goldman, Greenberg, & Pos, ; Pos, Greenberg, Goldman, & Korman, ). Previous research on ISTDP has also indicated that a high degree of MUCE in treatment (i.e., an “unlocking of the unconscious”) is associated with better outcome in mixed patient samples (Johansson, Town, & Abbass, ; Town, Abbass, & Bernier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with higher QOR may enter treatment with expectations of being responded to in a reasonable manner, thus deriving less of a corrective relational experience and perhaps utilizing other aspects of the program-such as insight (Jennissen, Huber, Ehrenthal, Schauenburg, & Dinger, 2018), affect (Diener, Hilsenroth, & Weinberger, 2007), or social rehabilitation activities (Korostiy, Kozhyna, & Zelenskaya, 2013) to foster more adaptive self-appraisals. These patients, whose lifelong relational patterns were relatively more coherent and stable, fared just as well as low-QOR patients in self-esteem improvement over the course of treatment.…”
mentioning
confidence: 99%